Acquisition of Bottled Water Among US Households. (29th May 2020) - Onufrak, Stephen; Chevinsky, Jennifer; Cradock, Angie; Poole, Mary Kathryn; Park, Sohyun
Abstract: Objectives: While drinking plain water instead of sugar-sweetened beverages (SSB) may improve diet and prevent diseases, bottled water is more costly than tap water and typically does not contain fluoride for oral health benefits. We explored bottled water acquisition among US households and its relationship with SSB acquisition. Methods: We used data from the USDA Food Acquisition and Purchasing Survey, which collected 7 days of data on all foods purchased or obtained for free in a nationally representative sample of 4826 households during 2012. Data were collected using food record books and bar code scanners. We assessed the prevalence of acquiring bottled water to bring home and for immediate consumption away from home, volume of water acquired, money spent on water, and the association of water acquisition with SSB acquisition. Differences in prevalence according to race/ethnicity, Census region, education level, rural status, and income/SNAP status were assessed using Chi-square tests. Adjusted linear models were used to assess the association of acquiring water for home or away from home with per-capita household total SSB calories acquired. Results: A quarter (24.6%) of households acquired any bottled water during the study week with 16.2% acquiring water for home and 11.1% away from home. Prevalence of acquiring any bottled water differed by region and race/ethnicity and was highest among households in the South and West (each 26.8%) and among Hispanic households (35.2%). Among those that acquired each type, households spent $4.13 acquiring 14.1 liters of water for home, while households spent $1.65 acquiring 2.0 liters for away from home. In regression models, households that acquired bottled water for home had greater per capita SSB calorie acquisition than households that did not (adjusted mean: 1203 vs. 734 kcal/week; P  = 0.0005); acquiring water for away from home was not associated with greater per capita SSB calorie acquisition (adjusted means: 931 vs. 1005 kcal; P  = 0.34). Conclusions: One quarter of US households acquire bottled water though acquisition differs according to demographic factors. Although plain water can reduce caloric intake when substituted for SSB, findings suggest that households that acquire bottled water for home also acquire more SSB calories than households that do not. Funding Sources: Solely for authors time from their institutions.